2022
DOI: 10.3390/foods11050756
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Approaches against Escherichia coli O157:H7 in Foods

Abstract: Shiga-toxin-producing Escherichia coli O157:H7 is a well-known water- and food-borne zoonotic pathogen that can cause gastroenteritis in humans. It threatens the health of millions of people each year; several outbreaks of E. coli O157:H7 infections have been linked to the consumption of contaminated plant foods (e.g., lettuce, spinach, tomato, and fresh fruits) and beef-based products. To control E. coli O157:H7 in foods, several physical (e.g., irradiation, pasteurization, pulsed electric field, and high-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 138 publications
0
16
0
Order By: Relevance
“…The primary criteria for selecting a biocontrol agent include having high antagonistic activity against the pathogens, safety for human consumption, and not interfering with the nutritional and organoleptic attributes of the dairy products (Ali et al ., 2019; Fahim et al ., 2021). Bio-agents, such as probiotics have the potential to exert an antagonistic effect against different strains of E. coli in addition to degrading their toxins (Puligundla and Lim, 2022). In various studies, probiotics were shown to remove toxins or toxins-producing pathogens by disrupting or changing the permeability of the plasma membrane, inhibiting protein translation, or preventing the binding receptors (Murray et al ., 2020; Ghadaksaz et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The primary criteria for selecting a biocontrol agent include having high antagonistic activity against the pathogens, safety for human consumption, and not interfering with the nutritional and organoleptic attributes of the dairy products (Ali et al ., 2019; Fahim et al ., 2021). Bio-agents, such as probiotics have the potential to exert an antagonistic effect against different strains of E. coli in addition to degrading their toxins (Puligundla and Lim, 2022). In various studies, probiotics were shown to remove toxins or toxins-producing pathogens by disrupting or changing the permeability of the plasma membrane, inhibiting protein translation, or preventing the binding receptors (Murray et al ., 2020; Ghadaksaz et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Most outbreaks of E. coli O157:H7 throughout the world in the recent past have been associated with the consumption of undercooked beef (Puligundla & Lim, 2022), thus using preservatives to inhibit the growth of E. coli O157:H7 on beef is of great importance. In our study, we found that cocktails of nisin and PA can efficiently kill planktonic and biofilm cells of E. coli O157:H7.…”
Section: Antimicrobial Activity Of Nisin And/or Pa Against Ecoli O157...mentioning
confidence: 99%
“…EHEC O157:H7, in particular, is one of the major foodborne pathogens worldwide and can cause fatal infections. Even a very low dose (50-100 CFU/g or ml) of EHEC O157:H7 can cause serious human diseases (Forghani et al, 2018;Puligundla and Lim, 2022). EHEC O157:H7 infection is characterized by severe hemorrhagic colitis and hemolytic uremic syndrome (HUS) in humans (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical (e.g., antibiotics, disinfectants, and organic acids) and physical (e.g., irradiation, pasteurization, pulsed electric field, and high-pressure processing) control strategies have been widely applied to reduce and inhibit EHEC O157:H7 in the food industry (Chun et al, 2017;Minh et al, 2020;Guo et al, 2021;Puligundla and Lim, 2022). However, these methods suffer from severe major weaknesses (Minh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation